Understanding the Factors Influencing Adoption of Digital Banking in Emerging Markets: The Role of Perception and Personality Antecedents - Ntswaki Petunia Matlala (Journal of Marketing and Consumer Behaviour in Emerging Markets)
The emergence of digital banking has presented the banking industry with benefits and challenges. Although digital banking services provide customers with increased convenience and accessibility around the clock, many still struggle to grasp their ever-changing nature. To address this, a study was conducted to identify the main factors influencing the adoption of digital banking in South Africa. The study used an e-readiness framework that combined the innovation diffusion theory and trust in technology with the technology readiness index to measure consumers’ adoption of digital banking channels. The researcher applied quantitative methodology to answer the research question. The snowball sample required respondents to answer the questionnaire and pass it on to others in the network with bank accounts and mobile phones; 338 responses were accepted. Structural equation modelling was employed to test the proposed hypotheses. This study discovered that the adoption of digital banking services is influenced positively by relative advantage, observability, optimism towards technology, innovativeness and insecurity. Therefore, banks should develop user-friendly platforms with online support to encourage the adoption of digital banking. Future research can use qualitative or mixed method approaches to investigate how customers’ perceptions and personalities influence the adoption of digital in emerging markets.